2008
DOI: 10.1158/1535-7163.mct-07-2256
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the novel apoptotic and therapeutic activities of the histone deacetylase inhibitor romidepsin

Abstract: Histone deacetylase inhibitors (HDACi) are compounds that target the epigenome and cause tumor cell-selective apoptosis. A large number of these agents that have different chemical structures and can target multiple HDACs are being testing in clinical trials and vorinostat is now an approved drug for the treatment of cutaneous T-cell lymphoma. Although these agents are showing promise for the treatment of hematologic malignancies, it is possible that different drugs may have different mechanistic, biological, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…The pan-HDACi vorinostat and panobinostat modified survival, proliferation and differentiation, whereas the class-I-selective HDACi romidepsin predominantly reduced B-cell survival, leaving proliferation and differentiation intact. These selective differences are not unexpected, as romidepsin has been demonstrated to have a restricted set of targets when compared to pan-HDACi 47 and this specificity manifests at both the molecular 48 and functional level 49 .…”
Section: Discussionmentioning
confidence: 91%
“…The pan-HDACi vorinostat and panobinostat modified survival, proliferation and differentiation, whereas the class-I-selective HDACi romidepsin predominantly reduced B-cell survival, leaving proliferation and differentiation intact. These selective differences are not unexpected, as romidepsin has been demonstrated to have a restricted set of targets when compared to pan-HDACi 47 and this specificity manifests at both the molecular 48 and functional level 49 .…”
Section: Discussionmentioning
confidence: 91%
“…Similar protection from chemotherapeutic drug-induced apoptosis can be afforded by overexpression of any of the other prosurvival BCL-2 family members. [134][135][136][137] Studies using gene-targeted mice or RNAi-mediated gene knockdown in cell lines revealed which pro-apoptotic BCL-2 family members are critical for cell killing by which anticancer agent. Consistent with the notion that BAX and BAK have essential overlapping functions in the BCL-2-regulated apoptotic pathway, cells from Bax −/− Bak −/− mice are markedly resistant to diverse anticancer agents.…”
Section: The Role Of the Bcl-2-regulated Apoptotic Pathway In Cancer mentioning
confidence: 99%
“…In vitro cell death and apoptosis analysis by flow cytometry Em-myc lymphoma cells (1 Â 10 5 ) were treated with compounds for 16 h in 96-well trays and the cell viability assessed by staining with 1 mg/ml propidium iodide (Sigma Aldrich Co, St Louis, MO, USA) (Newbold et al, 2008) and flow cytometry using the BD LSRII. Data were analysed using FACSExpress.…”
Section: Cell Culture and Transductionsmentioning
confidence: 99%
“…These data were used to calculate a best fit sigmoid dose-response curve using the statistical computing program 'R' (R DCT, 2009). Em-myc cells treated for 5 h were assessed for Annexin V APC (Becton Dickinson), and propidium iodide staining or assessed for DCM (MOMP) using tetramethyl-rhodamine ethyl ester (Invitrogen, Molecular Probes, Eugene, OR, USA) staining as described previously (Newbold et al, 2008). Cell cycle was analysed by DNA staining using propidium iodide on cells fixed in 95% ethanol at various times following drug treatment (Lindemann et al, 2007).…”
Section: Cell Culture and Transductionsmentioning
confidence: 99%